PENGARUH SELF-CONCEPT AKADEMIK TERHADAP KEMANDIRIAN BELAJAR SISWA KELAS VI SEKOLAH DASAR SELAMA PANDEMI COVID-19 - Archi Maulyda, Mohammad; Indraswati, Dyah; Erfan, Muhammad; Widodo, Arif; Nikmah Rahmatih, Aisa (Unika Santu Paulus Ruteng, 2021)
This research aims to determine the influence of the academic self-concept on the independence of learning class VI students during the pandemic. Research in the background is a problem that many students lack self-reliance in learning at an elementary school education level, especially when online-based learning is enforced during the pandemic. In addition, when exams are many students who are unable to work on their own and ask a friend next to him when the exam is in progress. This research uses a quantitative-descriptive approach. This type of research is correlation research. The subject in this study amounted to 40 students. The variables studied are self-concept academic and self-learning independent students. Data is collected through the self-learning concept of academic and student self-reliance. From the analysis results using the correlation analysis of product-moment with the help of SPSS version 23.0, obtained R table results with N = 70 and ? = 5%, is 0.235. While the Rcount obtained the magnitude of 0.769, then Rcountdown > Rtabel (0,769 > 0,235), meaning there is a positive and significant influence, consequently Ho rejected and Ha accepted. So, in conclusion